A Questionnaire based Evaluation of the Awareness among Dental Practitioners on Minimally Invasive Approach for Superficial Enamel Stains - Rukhsaar Gulzar, Subash Sharma2 , Mahalakshmi3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present survey was conducted to evaluate the awareness among dental practitioners on a minimallyinvasive approach for treatment of superficial enamel defects.The cross-sectional survey was conductedamong 150 dental practitioners in India. Data was obtained by distributing a self designed pretestedquestionnaire which comprised 20 questions to assess the knowledge of the practitioners on various minimallyinvasive procedures to treat superficial enamel stains, its incorporation into routine practice and ways toimprove their skills. Results were obtained in the form of graphs and percentage. A chi square test was doneto determine the association of the responses with the type of practice. The results of the study revealedthat a fair number of practitioners were aware of the theoretical aspects of micro and macroabrasion butthe clinical incorporation into routine practice is low, 68% did not incorporate the technique in their routinedental practice. The chi square values to check the association between the responses and type of practicewere <0.001 which was highly statistically significant. The endodontists had better knowledge about thetechniques as compared to the general practitioners and they also incorporated the technique more routinelyas compared to the general practitioners.There was a general preference to first opt for a minimally invasivetechnique but the treatment plan varies from person to person.There is a need for knowledge upgradationsand further clinical training through continuing dental education.